2007
DOI: 10.1051/0004-6361:20078289
|View full text |Cite
|
Sign up to set email alerts
|

WEBT and XMM-Newton observations of 3C 454.3 during the post-outburst phase

Abstract: Context. The quasar-type blazar 3C 454.3 was observed to undergo an unprecedented optical outburst in spring 2005, affecting the source brightness from the near-IR to the X-ray frequencies. This was first followed by a millimetric and then by a radio outburst, which peaked in February 2006. Aims. In this paper we report on follow-up observations to study the multiwavelength emission in the post-outburst phase. Results. The source was in a faint state. The radio flux at the higher frequencies showed a fast decr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
88
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 100 publications
(98 citation statements)
references
References 40 publications
9
88
1
Order By: Relevance
“…For instance, 3C 454.3 shows approximately the same spectral slope in different brightness states (see e.g. Raiteri et al 2007;Raiteri et al 2008). …”
Section: Swift/xrt Datamentioning
confidence: 97%
“…For instance, 3C 454.3 shows approximately the same spectral slope in different brightness states (see e.g. Raiteri et al 2007;Raiteri et al 2008). …”
Section: Swift/xrt Datamentioning
confidence: 97%
“…Through the analysis of low-energy data from the Whole Earth Blazar Telescope 1 (WEBT) and highenergy data from the XMM-Newton satellite, Raiteri et al (2007) were able to recognise both a little blue bump in the optical, possibly due to emission lines from the BLR, and a UV excess, suggesting a big blue bump likely due to thermal radiation from the accretion disc. Moreover, they argue that the X-ray spectrum may be concave, with spectral softening at lower energies becoming more evident when the source is fainter, maybe revealing the high-frequency tail of the big blue bump.…”
Section: Introductionmentioning
confidence: 99%
“…3C 454.3: This source is studied by Donato et al (2005) and found that it is well described by simple power law with Γ=1.34. XMM−Newton observations are analyzed by Raiteri et al (2007); 2008 in its post outburst and outburst states, respectively. We analysed four observations of XMM−Newton and found that all are well described by the power law model.…”
Section: S4 0954+65mentioning
confidence: 99%